2015
DOI: 10.1097/mib.0000000000000534
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Antibiotic Exposure and Clinical Disease Activity in Inflammatory Bowel Disease

Abstract: The majority of patients with IBD receive antibiotic treatment, and these individuals demonstrate a more severe clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…These findings suggest that antibiotic-induced dysbiosis of colon microbiota can modulate the immune response in the gut. Consistent with our findings a recent prospective observational study [89] reported that antibiotic exposure over the 4-year study period in patients with IBD for both IBD and non-IBD-related reasons is associated with the more severe clinical presentation. Antibiotic-exposed patients have an elevated rate of C-reactive protein compared with nonantibiotic-exposed patients, which indicates increased inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest that antibiotic-induced dysbiosis of colon microbiota can modulate the immune response in the gut. Consistent with our findings a recent prospective observational study [89] reported that antibiotic exposure over the 4-year study period in patients with IBD for both IBD and non-IBD-related reasons is associated with the more severe clinical presentation. Antibiotic-exposed patients have an elevated rate of C-reactive protein compared with nonantibiotic-exposed patients, which indicates increased inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…In line with the concept that a reduced abundance and the loss of certain taxa may be the consequence of antibiotic exposure, a recently published meta-analysis [60] demonstrated that an exposure to antibiotics appears to increase the odds of diagnosing CD but not UC. In addition, there is some evidence that the need for antibiotic treatment in IBD is associated with more severe disease course [61]. Although being plausible that short- and long-term changes in the composition of normal human microbiota affect the susceptibility and course of IBD, a causal relationship between antibiotic-induced dysbiosis and the development of IBD has not been proven yet.…”
Section: Antibiotics - Friend or Foe In The Pathogenesis And Course Omentioning
confidence: 99%
“…New research is focusing on the evaluation of the effectiveness of biological therapies within our patient cohort. We are also dedicating research efforts on quality of care metrics including the management of surveillance colonoscopies in patients with colonic IBD, infection rates, medication exposure, and the frequency and outcomes related to micronutrient repletion [40, 41]. Furthermore, the infrastructure currently afforded by this registry allows application of machine learning algorithms to discover patterns in the data.…”
Section: Discussionmentioning
confidence: 99%